Exploration of Symbiont Bacteria Potentially Degrading Chlorpyrifos Insecticide in the Digestive Tract of Beet Armyworm (Spodoptera exigua) in Kediri Regency - Widjayanti, Tita; Hadi, Mochammad Syamsul; Tantri, Zalfa Meiska (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2023)
Spodoptera exigua Hubner (Lepidoptera: Noctuidae) is an important pest on shallot crops and cosmopolitan with a fast life cycle. In controlling S. exigua farmers use chemical insecticides such as chlorpyrifos. Intensive application of insecticides causes resistance of S. exigua. Resistance can occur due to several factors, one of which is biological factors. In biological factors, there is a symbiosis between pests and beneficial bacteria called symbiont bacteria. It is suspected that symbiont bacteria symbiotic with S. exigua can degrade chlorpyrifos. The research was conducted from December 2022 to May 2023. The research began with a site survey and sampling in three sub-districts in Kediri Regency, namely Plemahan District, Kepung District, and Badas District. Furthermore, samples of S. exigua were studied at the Pesticide Toxicology Laboratory, Brawijaya University. The research conducted includes (1) exploration, isolation, and purification of symbiont bacteria in the digestive tract of S. exigua, (2) bioassay test of symbiont bacteria that have the potential to degrade chlorpyrifos, and (3) characterization of bacteria that have the potential to degrade chlorpyrifos. The results of the exploration of symbiont bacteria in the digestive tract of S. exigua obtained as many as 45 isolates of bacteria capable of growing in NA + chlorpyrifos media. Furthermore, from bioassay testing, 14 isolates of bacteria that have the potential to degrade chlorpyrifos insects. The characterization results showed that bacterial isolates that have the potential to degrade chlorpyrifos insecticides come from the genera Pantoea, Erwinia, and Coryneform.